Penanganan PPKS Melalui Layanan Terintegrasi di Rumah Singgah di Dinas Sosial Kota Medan - Yarli, Yosi; Triyani, Emi; Ritonga, Fajar Utama (Medan Resource Center, 2023)
This article discusses the handling of Social Psychological Disorder (PPKS) through integrated services at the Shelter House in the Medan City Social Office. This effort represents a systematic step in providing assistance and support to individuals experiencing social psychological disorders in Medan City. The Shelter House serves as a facility providing integrated services for PPKS individuals, covering various aspects of rehabilitation, counseling, mentoring, and social reintegration. The concept and implementation of integrated services at the Shelter House are outlined in this article, with an emphasis on the importance of a holistic approach to handling PPKS. Recent data and findings are presented to support arguments about the effectiveness and relevance of this approach in improving the quality of life for individuals affected by PPKS in Medan City.